Nicotinamide adenine dinucleotide assisted direct electrodeposition of gold nanodendrites and its electrochemical applications - Das, Ashok Kumar; Samdani, Jitendra; Kim, Hak Yong; Lee, Joong Hee (Electrochimica acta, 2015)
The shape tailoring in gold (Au) nanostructures is vital for tuning their optical and catalytic properties. Herein, we describe nicotinamide adenine dinucleotide (NAD+) assisted direct electrochemical growth of surface-confined Au nanodendrites as well as the application of these nanodendrites in the non-enzymatic detection of glucose in neutral pH and the oxidation of methanol in alkaline pH. NAD+ plays an important role in the growth of Au nanodendrites. The specific adsorption of NAD+ onto the Au (011) facet aids in the growth of Au nanodendrites. In the absence of NAD+, interconnected wall-like morphology is obtained. The Au nanodendrites are characterized by UV–visible spectroscopy, X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and electrochemical methods. FESEM and TEM analysis confirm that the Au nanostructures are dendritic, consisting of a trunk from which several branches evolve; the presence of NAD+ in the supporting electrolyte solution plays a vital role in the evolution of this morphology. The electrode based on Au dendrites has an electrochemically accessible surface area of 0.281cm2 and shows excellent electrocatalytic activity for both glucose and methanol. In alkaline pH, the Au nanodendrite-based electrode oxidized methanol at 0.3V with a highly-stable response. This electrode oxidizes glucose at 0.4V in neutral pH without the use of enzymes. The sensitivity and limit of detection of the electrode are calculated to be 0.037±0.02μAmM−1cm−2 and 7.29μM (S/N=3), respectively. The surface morphology of the Au nanostructure plays an important role in the electrocatalytic performance.